Progesterone-Related Immune Modulation of Pregnancy and Labor - Shah, Nishel M.; Lai, Pei F.; Imami, Nesrina; Johnson, Mark R. (Frontiers in Endocrinology, 2019)
Pregnancy involves a complex interplay between maternal neuroendocrine and immunological systems in order to establish and sustain a growing fetus. It is thought that the uterus at pregnancy transitions from quiescent to laboring state in response to interactions between maternal and fetal systems at least partly via altered neuroendocrine signaling. Progesterone (P4) is a vital hormone in maternal reproductive tissues and immune cells during pregnancy. As such, P4 is widely used in clinical interventions to improve the chance of embryo implantation, as well as reduce the risk of miscarriage and premature labor. Here we review research to date that focus on the pathways through which P4 mediates its actions on both the maternal reproductive and immune system. We will dissect the role of P4 as a modulator of inflammation, both systemic and intrinsic to the uterus, during human pregnancy and labor.